Enter the drag dragon [videorecording (Blu-Ray + DVD)] - Pollesel, Mark; Kellerman, Sam; London, Jade; Miwa, Matt; Beres, Beatrice; Caracas, Phil; Macdonald, Mark; Grace, Josh; Naftel, Kirby; Taylor, Quintana; Moreno, Natalia; Kaufman, Lloyd, 1945-; et al. (MVDvisual, 2024)
"Get ready to go on a Drag-Fu odyssey, filled with face-crunching action, corset-busting comedy, gut-munching horror, soul-touching musical numbers. You've never experienced anything like Enter the Drag Dragon!... Crunch is a part-time amateur detective, and full-time drag queen. His lifelong best friend is Jaws, a roller-skaing entrepreneur and fast-food delivery girl. The oddball pair has been through a lot of their lives, but are as close as siblings. They are no strangers to fast times, adventure, and action."--Container.